Capital budgeting practices in hospitals. (30th September 2005) - Smith, Dean G.; Wynne, Joshua
We interviewed chief financial officers from hospitals and healthcare systems in Michigan regarding selected capital budgeting practices that have not been previously considered in the literature. Results revealed a variety of approaches in the development and deployment of capital budgets. Most healthcare systems used a blend of board and department-initiated input into budget development, usually with interaction between the two. The majority of healthcare systems had flexibility in the deployment of their capital budgets over time. Standard methods of project evaluation were employed by healthcare CFOs, but few used the most sophisticated tools. A host of constraints, including certificate-of-need laws and internal, mission-based motivations uniquely affect capital budgeting of not-for-profit healthcare systems. Clearly, future research will be need to understand why organisations have selected capital budgeting practices and the extent to which selection and use of capital budgeting practices matters in the efficiency and viability of healthcare systems.